Pneumonia immunization in older adults: review of vaccine effectiveness and strategies - Assaad U (Dove Medical Press, 2012)
Usama Assaad,2 Ibrahim El-Masri,2 Jahan Porhomayon,1,3 Ali A El-Solh1–41The Veterans Affairs Western New York Healthcare System, Buffalo, NY, USA; 2Division of Pulmonary, Critical Care, and Sleep Medicine, 3Department of Anesthesia, 4Department of Social and Preventive Medicine, State University of New York at Buffalo School of Medicine and Biomedical Sciences and School of Public Health and Health Professions, Buffalo, NY, USAAbstract: Vaccination remains the primary preventive strategy in the elderly against Streptococcus pneumoniae and influenza infections. The effectiveness of this strategy in preventing pneumonia has been in doubt despite the increase in vaccination coverage among older adults. Randomized controlled trials (RCTs) and observational studies aimed at determining clinical outcomes and immune response following pneumococcal vaccination have yielded conflicting results. The protective efficacy of pneumococcal vaccination against pneumonia in older adults has not been firmly established due to a lack of RCTs specifically examining patients ≥ 65 years of age. Similarly, the reported benefits of influenza vaccination have been derived from observational data. The assessment of clinical benefit from influenza vaccination in the elderly population is complicated by varying cohorts, virulence of the influenza strain, and matching of vaccine and circulating viral strains. The presence of selection bias and use of nonspecific end points in these studies make the current evidence inconclusive in terms of overall benefit. The development of more immunogenic vaccines through new formulations or addition of adjuvants holds the promise of revolutionizing delivery and improving efficacy. Dismantling existing barriers through education, providing technology assistance predominantly to developing countries, and establishing clear regulatory guidance on pathways for approval are necessary to ensure timely production and equitable distribution.Keywords: pneumococcal vaccine, influenza vaccine, vaccine effectiveness, pneumonia, older adults